The Consolidation of the Angola—Zambia Border: Violence, Forced Displacement, Smugglers and Savimbi. Issue 3 (3rd July 2017) - Neto, Pedro Figueiredo
ABSTRACT: The Angola-Zambia borderlands remain a territory of scarce research—a scientific vacuum largely justified by the uncertain history of this region. Thus, based on fieldwork conducted along both sides of the border between Zambia and Angola, this paper aims to introduce some of the key events on the genesis of the international demarcation and its gradual consolidation. The purpose is to analyze the substance of the border, the borders—old and new—within that same territory. If in the past the border was virtually non-existent, today a myriad of not always evident mechanisms and situations compose and give meaning to this borderscape. Over time, slavery, forced labor, violence and high taxes accentuated the colonial limits by establishing a very clear demarcation between dispossession and survival. After five centuries of Portuguese rule, Angola endured one of the deadliest conflicts in recent history (1961–2002). Wartime episodes, forced displacement, border smuggling and the spectrum of Jonas Savimbi—the deceased Angolan rebel leader—enlarged the border imaginary.